2017
DOI: 10.19080/ijesnr.2017.04.555650
|View full text |Cite
|
Sign up to set email alerts
|

"A Comprehensive Phytopharmacological Review of Dioscorea bulbifera Linn"

Abstract: Dioscorea bulbifera Linn. is an important medicinal plant, which has long been used in traditional Indian and Chinese medicine for various diseases. This plant is pharmacologically studied for antitumor, anti HIV, antidyslipidemic, analgesic, anti-inflammatory, diuretic, gastroprotective, antioxidant, antimicrobial, antiviral, antifungal, anthelmintic, neuropharmacological, cardioprotective, anorexiant, plasmid curing activities and anti-hyperthyroid activities. A wide range of phytochemical constituents have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…They were found to have a pronounced immunomodulating effect influencing different lymphocyte subpopulations. Experiments on isolated leukocyte cell cultures revealed that the effect of SG was concentration-dependent: different SG levels either stimulated or suppressed immune response [13][14][15][16]. The ability of Dioscorea spp.…”
Section: Introductionmentioning
confidence: 99%
“…They were found to have a pronounced immunomodulating effect influencing different lymphocyte subpopulations. Experiments on isolated leukocyte cell cultures revealed that the effect of SG was concentration-dependent: different SG levels either stimulated or suppressed immune response [13][14][15][16]. The ability of Dioscorea spp.…”
Section: Introductionmentioning
confidence: 99%